Socialization of the Use of Long-Term Contraceptive Methods (LTCM) in Women of Reproductive Age (WRA) - Dahniar, Dahniar; Kadir, Arisna; Hasnaeni, Hasnaeni (Jurnal Abmas Negeri (JAGRI), 2025)
Long-term contraceptive methods (LTCM) are methods designed to prevent pregnancy over a long period of time. According to WHO (2019), of the 1.9 billion women of childbearing age (15-49 years) in the world, around 1.1 billion require family planning services. There are 406 million modern contraceptive users, consisting of 159 million IUDs, 23 million implants, 74 million injections, and 150 million pills. This activity aimed to increase Women of Reproductive Age (WRA) knowledge about LTCM through socialization. The activity began with the licensing process, preparation of leaflet media containing LTCM information and scheduling of implementation. The activity was carried out at the integrated health post in the Bara-Barayya Health Center working area on June 28, 2024 assisted by a coordinating midwife and cadres with 23 WRA participants. The socialization carried out included pre-tests and post-tests, delivery of material on the types, benefits, risks, and how to use LTCM, as well as interactive discussions and questions and answers to encourage active participation of participants. Evaluation was carried out to measure the increase in knowledge. Before socialization, 18 (78,3%) had good knowledge, 5 (21,7%) had poor knowledge. After socialization, 21 (91,3%) had good knowledge and only 2 (8,7%) had poor knowledge. In conclusion, there was an increase in knowledge after socialization. Continued support and attention are needed so that the use of LTCM P is effective in regulating pregnancy spacing and preventing unwanted pregnancies. WRA are advised to continue to increase their knowledge of contraceptive methods.